SUPERVISION OF VILLAGE-OWNED ENTERPRISES (BUMDES) MANAGEMENT IN IMPROVING THE COMMUNITY'S ECONOMY IN TOULUAAN DISTRICT, SOUTHEAST MINAHASA REGENCY - Debora Regina Pelealu; William Areros; Femmy M.G. Tulusan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the process of supervising the management of Village-Owned Enterprises (BUMDes) in improving the community's economy in Touluaan District, Southeast Minahasa Regency. This research uses a qualitative descriptive method based on the theory of supervision with indicators consisting of setting standards for implementation or planning, work measurement, performance appraisal and corrective action. There were a total of 10 participants who took part as informants in the study. Data collection was carried out by means of observation, interviews and documentation which were analyzed using data reduction, data presentation and drawing conclusions. The results of this study indicate that in carrying out the management of BUMDes, the villages that manage the BUMDes have planning in accordance with supervisory standards carried out both by the internal government and by the internal BUMDes itself which involves the community. The work measurement process as part of the supervision of the management of village-owned enterprises is carried out by means of BUMDes managers providing reports in writing both to internal supervisors and to internal supervisors as a form of implementation responsibility that involves the community. However, the Village Government does not fully involve the community in order for people who can become internal and external supervisors in earth management to provide information that can be input for supervisors to provide corrective actions to BUMDes managers.